Trends in the Airglow Temperatures in the MLT Region—Part 1: Model Simulations - Tai-Yin Huang; Michael Vanyo (Atmosphere, 2020)
Airglow intensity-weighted temperature variations induced by the CO2 increase, solar cycle variation (F10.7 as a proxy) and geomagnetic activity (Ap index as a proxy) in the Mesosphere and Lower Thermosphere (MLT) region were simulated to quantitatively assess their influences on airglow temperatures. Two airglow models, MACD-00 and OHCD-00, were used to simulate the O(1S) greenline, O2(0,1) atmospheric band, and OH(8,3) airglow temperature variations induced by these influences to deduce the trends. Our results show that all three airglow temperatures display a linear trend of ~−0.5 K/decade, in response to the increase of CO2 gas concentration. The airglow temperatures were found to be highly correlated with Ap index, and moderately correlated with F10.7, with the OH temperature showing an anti-correlation. The F10.7 and Ap index trends were found to be ~−0.7 ± 0.28 K/100SFU and ~−0.1 ± 0.02 K/nT in the OH temperature, 4.1 ± 0.7 K/100SFU and ~0.6 ± 0.03 K/nT in the O2 temperature and ~2.0 ± 0.6 K/100SFU and ~0.4 ± 0.03 K/nT in the O1S temperature. These results indicate that geomagnetic activity can have a rather significant effect on the temperatures that had not been looked at previously.